Character Values ​​of Islamic Education in the Novel "Laskar Pelangi" By Andrea Hirata: Nilai-Nilai Karakter Pendidikan Islam Dalam Novel “Laskar Pelangi” Karya Andrea Hirata - Eka Aprilia; Anita Pujiastutik (Academia Open, 2021)
The purpose of this research is to determine the values ​​of the character of Islamic education in the novel Laskar Pelangi by Andrea Hirata, to increase knowledge about the values ​​of educational characters in the novel Laskar Pelangi by Andrea Hirata. This researcher can also provide benefits for readers to motivate when taking an education.The method in this thesis uses qualitative research because the data collected is presented in the form of verbal words instead of numbers. This research is included in library research (library research), namely by using literature (literature), reading notes, analyzing research materials in the form of books, notes, journals and the internet. This study found four character values ​​of Islamic education in Andrea Hirata's novel Laskar Pelangi, namely: aqidah value, worship value, moral value, and finally, social value.